Physiological Stress Response Reactivity Mediates the Link Between Emotional Abuse and Youth Internalizing Problems - Duprey, Erinn Bernstein (Child Psychiatry Hum Dev, 2021)
Youth who are raised in emotionally abusive families are more likely to have poor mental health outcomes such as depression and anxiety. However, the mechanisms of this association are unclear. The present study utilized a longitudinal sample of low-SES youth (N = 101, M(ageT1) = 10.24) to examine stress response reactivity (i.e., vagal withdrawal, sympathetic activation, and hypothalamic-pituitary-adrenal [HPA] axis activation) as mediators between emotional abuse and prospective youth internalizing symptoms. Results indicated that blunted HPA reactivity to a laboratory social stress task mediated the association between emotional abuse and youth internalizing symptoms. Emotional abuse was also associated with blunted parasympathetic nervous system activity (i.e., less vagal withdrawal than average). In sum, emotional abuse is a potent risk factor for youth internalizing symptoms, and this link may be mediated via dysregulation in physiological stress response systems. Primary prevention of childhood emotional abuse and secondary prevention programs that target self-regulation skills may reduce rates of youth internalizing symptoms and disorders.